Intersection of Stress, Social Disadvantage, and Life Course Processes: Reframing Trauma and Mental Health - Nurius, Paula S. (Am J Psychiatr Rehabil, 2013)
This paper describes the intersection of converging lines of research on the social structural, psychosocial, and physiological factors involved in the production of stress and implications for the field of mental health. Of particular interest are the stress sensitization consequences stemming from exposure to adversity over the life course. Contemporary stress sensitization theory provides important clinical utility in articulating mechanisms through which these multiple levels exert influence on mental health. Stress sensitization models (a) extend understanding of neurobiological and functional contexts within which extreme stressors operate and (b) make clear how these can influence psychologically traumatic outcomes. The value of interventions that are sensitive to current contexts as well as life course profiles of cumulative stress are illustrated through recent treatment innovations.